ROLA ANALIZY POTRZEB I EWALUACJI KURSU W NAUCZANIU JĘZYKA SPECJALISTYCZNEGO - Lesiak-Bielawska, Elżbieta Danuta (Neofilolog, 2020)
The objective of the present paper is to discuss pre-course needs analysis and post-course evaluation, and their role in teaching Language for Specific Purposes. Though these two key stages have different aims and perspectives, they should not be treated as separate, linearly-related activities but rather as overlapping and interdependent phases of LSP course design. The repeated needs analysis that is built into the formative evaluation process contributes to making the resultant LSP course more responsive to the needs of the learner group.